THE CHORAL FRAMEWORK IN THE OPERA DECEBAL BY TEODOR ZGUREANU - Luminiţa GUŢANU (Studia Universitatis Babeş-Bolyai. Musica)
Zgureanu’s entire work is influenced by the folkloric ethos. On the whole, the resort to the folkloric substance is one of the constant features of his work. For the most part, he uses rhythmic-melodic elements specific to the folkloric melodicity, elements that draw their essence from the century-long experience of the folk artist that he decants by subjecting them to his own, unmistakable language. The multiple-level contrasts (dynamic, rhythmic, timbral, of registers), the vitality, energy, tension, harshness and density are the main characteristics of this opera, in which we find clarity and self-confidence in composition, build-ups and tensions disrupted by breaks or by contrasting sections, but also a persistency in using melodic-rhythmic cells of folk origin. It is a style the composer has perfected with great toil, characterized also by timbral refinement and subtlety in the game of nuances. The entire structure is built either upon agglomerations or rarefactions, or upon sudden disruptions and contrasts.